Tachycardia during the onset of one-kidney, one-clip renal hypertension: role of the renin-angiotensin system and AV3V tissue - Menani, JoséV. [UNESP]; Machado, Benedito H.; Krieger, Eduardo M.; Salgado, Hélio C. (Elsevier, 1988)
We have previously demonstrated a transitory tachycardia during the early phase of one kidney, one clip (1K1C) hypertension in the rat, when the basal heart rate (HR) is measured daily under resting conditions. In the present study, in control rats, marked tachycardia (406 ± 11 vs 320 ± 4 bpm during the control period) was observed on the first day of electrolytic lesion of the anteroventral third ventricle (AV3V) region. The basal HR declined progressively thereafter and was normal 14 days after AV3V lesion. The peak of tachycardia (388 ± 12 bpm) observed 7 days after clipping in sham-lesioned rats did not occur in 1K1C AV3V-lesioned rats (318 ± 5 bpm). However, hypertension was only partially (65%) abolished in the lesioned animals (135 ± 4 vs 160 ± 3 mm Hg in the sham-lesioned 1K1C). Captopril administered per os (30 mg/kg/day) for up to 20 days produced no change in the basal HR of sham-operated rats but abolished the initial tachycardia in 1K1C rats during the development of hypertension. Captopril also delayed the onset of renal hypertension, with mean arterial pressure reaching hypertensive levels only 2 weeks after clipping. These data indicate that integrity of the AV3V region is necessary for the occurrence of tachycardia during the onset of 1K1C hypertension. Since captopril abolished the tachycardia, the activity of converting enzyme seems to be important for the appearance of this phenomenon. © 1988.
Keywords: Angiotensin II; Baroreflex; Basal heart rate; Blood pressure regulation; Captopril; Converting enzyme inhibitor; Sympathetic nervous system